Structural adjustment recent policy developments: the Trinidad and Tobago experience: country paper (ILO. PREALC Caribbean Office Port of SpainTT, 1991)
Identifies the major domestic and external factors which attributed to the loss in foreign exchange resources between the period 1982-1988. Considers the objectives and identifies 6 components of the structural adjustment programme viz. exchange rate adjustment; fiscal reform; public sector reform; trade and investment liberalisation; monetary management; and external debt rescheduling.IIdentifies some of the measures adopted by Government for ameliorating the hardships on the population and for ensuring better targeted intervention.
DC